Effects of chlorpyrifos on acetylcholinesterase activity in the brain, plasma and red blood cell of Nile tilapia (Oreochromis niloticus) (Thai) - Nittayachit, Pittaya; Chanthai, Saksit; Petkam, Rakpong (Asia-Pacific Journal of Science and Technology, 2017)
Effects of chlorpyrifos on acetylcholinesterase (AChE) activity in the brain, plasma and red blood cells of Nile tilapia (Oreochromis niloticus) were investigated using 160 mixed sex Nile tilapia. Fish were allocated into glass aquaria using 10 fish each. Treatments were applied by exposing to chlorpyrifos at 0, 0.025, 0.25 and 2.5 microgram/liter with 4 replications. The brain, plasma and red blood cell samples were collected at 0, 24, 48, 72 and 96 hours after chlorpyrifos exposure, followed by determination of AChE activity. It was found that the AChE activity of samples exposed to chlorpyrifos was generally decreased and the degree of decrease correlated with dose applied.